ChemInform Abstract: Iodocyclization of Ethoxyethyl Ethers to Ynamides: An Immediate Construction to Benzo[b]furans. Issue 50 (16th December 2014) - Okitsu, Takashi; Nakata, Kohei; Nishigaki, Kenji; Michioka, Naoyuki; Karatani, Mitsuaki; Wada, Akimori
Abstract The title reaction is completed within three seconds.